PRES in eclampsia – Two clinical cases - Varejão, Ana (2024)
Eclampsia is the convulsive manifestation of hypertensive disorders of pregnancy. Posterior reversible encephalopathy syndrome (PRES) is characterized by a variety of neurological signs and symptoms as well as characteristic neuroimaging findings reflecting subcortical vasogenic edema, particularly in the posterior regions and typically reversible within days or weeks. The authors present two clinical cases of PRES in the setting of eclampsia. In the first case, a puerperal woman complained of persistent frontal headache associated with high blood pressure two days after delivery, which progressed to amaurosis and two episodes of generalized tonic-clonic seizures a few hours later. In the second case, a pregnant woman had an episode of tonic-clonic seizure with tongue biting during the third stage of labor without any preceding symptoms. These two cases underscore the heterogeneity of the clinical presentation of this syndrome and highlight the importance of maintaining a high index of suspicion for timely diagnosis and appropriate management, particularly given the potential reversibility of symptoms and imaging findings.